Rencana Aksi Implementasi Perubahan dalam Perusahaan - Widiawati Widiawati (GLOBAL SCIENTS PUBLISHER, 2025)
The implementation of change within a company is a critical and complex process to ensure the continuity and success of the organization in facing the ever-evolving dynamics of the business environment. Implementing change in a company involves trial processes, system adjustments, and direct adaptation. This journal discusses a systematic and structured action plan to effectively manage the change process. The main focus lies in identifying key success factors, designing implementation steps, the role of leadership, and efforts to mitigate challenges that arise during the process. The use of qualitative research methods through case studies provides an in-depth understanding of best practices in change implementation. The findings of this study are expected to serve as a strategic guide for company management in executing change effectively and efficiently.